The Specter of Digital Rights - K. I. Ryabov (Теоретическая и прикладная юриспруденция)
In the article, the author examines the problem of the impact of technological changes on the legal regulation of public relations, namely the development of digital technologies, how significant such an impact turned out to be and whether, in this regard, significant changes in the principles and mechanisms of legal regulation are required. It is asserted in the article that the problem how to adapt existing legal forms in order to address inevitable changes in public relationships (does not matter what the cause of these changes is: the so called “digitalization” or something else) may be relatively easily resolved. What we need to do is to segregate those aspects of the factual side of relationships in question that should have legal consequences from the rest, that is from those aspects that may be ignored by law. In order to illustrate this thesis the author considers two examples: the semiconductor chip protection and the electronic signature as a way to identify an entity who expressed a will. The author comes to the conclusion that the existing legal instruments for regulating the emerging new factual relations are sufficient, but they must be used correctly. The author gives examples of such law enforcement within the framework of the article.